2022
DOI: 10.3389/fcvm.2022.940808
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization of chronic total occlusion coronary artery and cardiac regeneration

Abstract: Coronary chronic total occlusion (CTO) contributes to the progression of heart failure in patients with ischemic cardiomyopathy. Randomized controlled trials demonstrated that percutaneous coronary intervention (PCI) for CTO significantly improves angina symptoms and quality of life but fails to reduce clinical events compared with optimal medical therapy. Even so, intervening physicians strongly support CTO-PCI. Cardiac regeneration therapy after CTO-PCI should be a promising approach to improving the prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 142 publications
0
2
0
Order By: Relevance
“…We then performed an enrichment analysis of the DEGs and discovered that the most enriched GO term under biological process was angiogenesis. Amir et al [ 26 ] reviewed pathological angiogenesis caused by endothelial cell dysfunction in COVID-19, and Liao et al [ 27 ] suggested that cell therapy could promote angiogenesis to improve ICM. We therefore speculated that angiogenesis may be one of the phenotypes of the co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…We then performed an enrichment analysis of the DEGs and discovered that the most enriched GO term under biological process was angiogenesis. Amir et al [ 26 ] reviewed pathological angiogenesis caused by endothelial cell dysfunction in COVID-19, and Liao et al [ 27 ] suggested that cell therapy could promote angiogenesis to improve ICM. We therefore speculated that angiogenesis may be one of the phenotypes of the co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic total occlusion (CTO) stands as a formidable clinical entity within the spectrum of coronary artery disease (CAD), characterized by the enduring occlusion of a coronary artery for a duration extending beyond three months [1]. The pathological significance of CTOs is underpinned by its potential to precipitate ischemia, diminishing quality of life and presenting as a conundrum in cardiovascular therapeutics due to the challenges it poses for medical and surgical management [2]. In response to the ischemic insult of CTOs, the heart initiates the formation of collateral vessels-a natural bypass system crucial for preserving myocardial perfusion [3].…”
Section: Introductionmentioning
confidence: 99%